The Effect of Customer Engagement on Purchase Intention in Kimia Farma Services in Surabaya - Elvarina, Elinda; Murhadi, Werner R. (Devotion : Journal of Research and Community Service, 2023)
purchase intention in Kimia Farma services in Surabaya. Data were collected through a survey with 106 respondents. The data used in this study is primary data obtained from online questionnaires. The respondents of this research are members of Kimia Farma who shop in in Kimia Farma. The sampling technique used was non-probability sampling. This research is quantitative research with statistical testing using Structural Equation Modeling (SEM) with Partial Least Square (PLS) is used to perform data analysis. In this study it was found that there is a positive influence between customer engagement and perceived value. There is a positive influence between customer engagement and customer satisfaction. There is a positive influence between customer engagement and purchase intention. There is a positive relationship between perceived value and customer satisfaction. There is a positive influence between perceived value and purchase intention. There is a positive influence between customer satisfaction and purchase intention. There is a negative influence between customer uncertainty and purchase intention.